PENGARUH STRATEGI ROUTE PLANNING TERHADAP KINERJA MARKETING PADA PT RASA PRIMA SELARAS - Ariyanto M; Widya Pratiwi (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2020)
The use of a Route Planning (SRP) strategy information system can support marketing performance improvement at PT. Rasa Prima Selaras. Because of this the researcher wants to test the extent of the influence of the Route Planning Strategy (SRP) on Marketing Performance and how much influence the Route Planning Strategy (SRP) has on marketing performance. The method in this research is to use the method through research activities. In research researchers used survey research with a quantitative approach. The population in this study is an outlet that is domiciled in the city of Muara Bungo, as many as 103 outlets. From the population, the sampling technique used is Totaly Sampling. Totaly Sampling is a sampling procedure in which the entire population is taken and made a respondent or sample. From the sampling technique, it was found that the samples in this study were 103 people. The use of Information Systems (X) has a significant effect on Marketing Performance (Y). Can be seen from the significant value of tcount ≥ ttable t, which is 2.830> 1.937 or the significance value (0.006) <α = (0.05), meaning that H is accepted. Where this shows the Use of Information Systems Strategies Route Planning (X) affect the Marketing Performance (Y) at PT. Rasa Prima Selaras.